Juridical Analysis Of The Commissioners Of Limited Liability Companies Who Exercise The Authority Of The Executive Board Of Directors In Terms Of Good Corporate Governance Aspects - Willem Engel Oktavianus Umboh; Ismail Ismail; Puguh Hari Setiawan (Publikasi Indonesia, 2024)
This study aims to explain the legal basis and functions of organs in a Limited Liability Company (PT) and identify the legal impact on PT organs that carry out the duties and authorities of other organs. In the global context, Good Corporate Governance (GCG) is the key to the company's success for long-term growth and business continuity. The economic crisis in Asia and Latin America in 1999 was attributed to the failure of GCG implementation. The research method used is normative juridical with an analytical descriptive approach. The two main approaches used are the statutory approach and the conceptual approach. The results showed that the executive actions of Commissioners in PT require approval from the Board of Directors with a power of attorney, maintain legality and implement the principles of Good Corporate Governance. The Bank as a third party also requests a power of attorney to ensure the legality of the applicant who is a Commissioner. Research reveals the legal basis for the establishment of a PT stipulated in Articles 36-56 of the Criminal Code and Articles 1233-1652 of the Civil Code. This research contributes to understanding the importance of GCG implementation and the legality of the Commissioners' executive actions in maintaining the integrity of the company. The results of the research are expected to be the basis for companies and regulators in improving good corporate governance.